Menafsir Genre Apokaliptik Kitab Daniel - Hasahatan Hutahaean (ILLUMINATE: Jurnal Teologi dan Pendidikan Kristiani, 2020)
The Apocalyptic genre is one genre that is difficult to understand because of its long intricacies and requires accuracy. One reason for the difficulty in interpreting the apocalyptic genre is the use of symbols that are not uncommon for today's readers. The use of symbols is very close to the speaker and, the first reader. The Book of Daniel is identical to the many uses of the symbolic language of the two Apocalyptic genre Books in the Bible. Readers increasingly need to be careful and careful when classifying symbol languages because there are differences in the use of symbols and language of descriptions. This paper was prepared by searching the literature with a qualitative approach. With the support of data from journal articles and cognate books, the research achieved the expected goals. The discussion begins by describing the apocalyptic genre based on literal facts. Then examine the uses of symbols, images, and others and the need for the interpreter's humility when trying to interpret this genre, especially in the use of symbolic language. The results show that many parts can be understood by following the rules of interpretation of the apocalyptic genre in the use of symbolic language. But some parts are precisely still a mystery to the reader as sealing of their meaning.AbstrakGenre Apokaliptik termasuk salah satu genre yang sulit untuk dipahami karena seluk-beluk yang panjang dan memerlukan ketelitian. Salah satu penyebab sulitnya menafsir genre apokaliptik yakni pemakaian simbol-simbol yang tidak lazim bagi pembaca masa kini. Pemakaian simbol-simbol sangat dekat bagi penutur dan pembaca pertamanya. Kitab Daniel identik dengan banyaknya pemakaian bahasa simbol dari dua Kitab genre apokaliptik dalam Alkitab. Pembaca semakin perlu berhati-hati dan teliti ketika mengelompokkan bahasa-bahasa simbol karena terdapat perbedaan penggunaan simbol dan bahasa penggambaran. Tulisan ini disusun dengan penelusuran kepustakaan dengan pendekatan kualitatif. Dengan dukungan data dari artikel jurnal dan buku-buku serumpun maka penelitian mencapai tujuan yang diharapkan. Pembahasan dimulai dengan memaparkan genre apokaliptik berdasar fakta-fakta literal. Kemudian menelisik penggunaan simbol, gambar dan yang lain serta perlunya kerendahan hati penafsir ketika mencoba menafsirkan genre ini khususnya dalam penggunaan bahasa simbol. Hasilnya menunjukkan banyak bagian yang dapat dipahami dengan mengikuti kaidah penafsiran bagi genre apokaliptik dalam pemakaian bahasa simbol. Namun ada bagian-bagian yang justru masih menjadi misteri bagi pembacanya sebagai penyegelan terhadap maknanya.